The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5603/fc.2019.0009
|View full text |Cite
|
Sign up to set email alerts
|

Interakcje wybranych leków kardiologicznych ze składnikami diety

Abstract: Starzejące się społeczeństwo i narastający problem wielochorobowości przyczyniają się do powstania potrzeby długotrwałego stosowania leków kardiologicznych, a co za tym idzie-zwiększa się ryzyko wystąpienia interakcji. Celem niniejszej pracy jest przedstawienie interakcji leków stosowanych w praktyce klinicznej kardiologa z żywnością. Działanie antagonistów witaminy K nasilają m.in.: szałwia, rumianek, natka pietruszki, anyż, lukrecja, imbir, żeń-szeń, sok żurawinowy i sok grejpfrutowy. Z kolei produkty bogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…It has been shown that ginseng interacts with medications, primarily by inhibiting the activity of cytochrome P450, responsible for metabolizing many drugs [53]. Ginseng interacts with anticoagulant drugs such as warfarin, acenocoumarol, and antiplatelet medications [67]. In both drug groups, the consumption of ginseng intensifies their effects, leading to an increase in bleeding complications in patients [68].…”
Section: State Of Knowledgementioning
confidence: 99%
“…It has been shown that ginseng interacts with medications, primarily by inhibiting the activity of cytochrome P450, responsible for metabolizing many drugs [53]. Ginseng interacts with anticoagulant drugs such as warfarin, acenocoumarol, and antiplatelet medications [67]. In both drug groups, the consumption of ginseng intensifies their effects, leading to an increase in bleeding complications in patients [68].…”
Section: State Of Knowledgementioning
confidence: 99%
“…Substancja aktywna zawarta w Ginkgo biloba -ginkgolid B hamuje czynnik aktywujący płytki krwi -PAF (ang. platelet activating factor), dzięki czemu wzmacnia działanie powyższych leków, jednocześnie zwiększając ryzyko krwawień i zdarzeń krwotocznych [26]. Z tego względu preparatów tych nie wolno stosować minimum tydzień przed planowaną operacją lub zabiegiem.…”
Section: Interakcje I Działania Niepożądane G Bilobaunclassified